Pentingnya Pengendalian Udara Lingkungan Untuk Pencegahan Transmisi SARS CoV2 - Trevino Aristarkus Pakasi; Levina S. Pakasi (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2020)
Introduction: The covid 19 pandemics in Indonesia has started in March 2020 but there is no sign of ending up till this publication. Aim of study: This is a narrative review to explain the importance of using HEPA filter as environmental control. Method: The study was a narrative review using recently published journals in 2020 about Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV2) transmission. Results and Discussion: The study in Wuhan found viral particles in the circulating air of the Covid 19 referral hospitals, especially where there was no sufficient air exchange. A similar finding was reported in a hospital in Nebraska. Particles of 2.5 microns in size as air pollutants increased the risk of fatality because the size made it possible to reach the alveoli, where viruses could attach with. The study in North Italy, Germany, and the United States found the synergy between the level of pollution to increase mortality of Covid 19 in that particular area. A HEPA filter is an old technology for the isolation room in a hospital, which has to be a standard in many rooms in a hospital that can filter the virus. Conclusion: Most of the findings suggested airborne transmission of SARS CoV2 and it is important to use HEPA filter in a closed office.